"Fuzis" educacionais da Senhora Carrar: "pastitura sobre o poste de armas na contemporaneidade a partir da dramaturgia de Brecht (1936)" - YOGAMA, Mauro (2022)
This work is based on the work and spectacle “The Rifles of Lady Carrar” by author Bertold Brecht, through questions that the presentation has as subthemes the possession of weapons, and having a correlation to a not too distant reality that Brazil can adopt The paper clarifies the consequences we would have socially if this law were to be approved. In addition to raising awareness, this paper aims to interview the cast of the play in order to know their opinions on the issue of possession / possession of weapons and how to know their opponents. of direct and indirect correlations aboutthe possession / possession of weapons may or may not have influence. In the end all respondents gave satisfactory answers about the theme as well as showed to have a great knowledge of the consequences either by influence or not of the participation of the show to which treats this theme as a subtheme.